Panama: News Coverage of the Digital Divide during the COVID-19 Pandemic - Urribarri, Raisa (2022)
This article reports on documentary research aimed at analyzing the coverage made by the Panamanian media about the digital divide during the first six months of the pandemic. Using Google's advanced search, a corpus of 140 pieces of information was extracted and analyzed using the criteria of newsworthiness and information sources. The results show an episodic and shallow coverage of a complex phenomenon that generated a wide social discontent in a society with high levels of inequality. Recommendations are offered that could contribute to a dissemination aimed at the understanding of this phenomenon as a by-product of social inequality, but also as a deepener of it.